MENINGKATKAN HASILBELAJAR SISWA KELAS XI IPA 2 MAN MODEL GORONTALO PADA MATERI HIDROLISIS GARAM DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION (GI) - Rasid, Meli A.; Bialangi, Nurhayati; Alio, La (Jurnal Entropi, 2009)
The research aimed to improve students achievement through Cooperative learning model of GI type in salt Hydrolysis lesson Material. It had done in students of 2008/2009 academic years that consisted of 20 students. Techniques in collecting data wereobservation sheet of teacher and students and test of students achievement. The research had to do second cycle,60% of students reached score less than 6,5. there it had to do second cycle. Second cycle was reparation of step and learning proses from first cycle.The result of second cycle showed that students achievement was improved to 95% and reached score standard more than 6,5. thereby, cooperative learning model of GI type in Salt Hydrolysis leason material can improve students achievement.